Utilización de harina de carne, como fuente de proteína animal, en raciones de engorde para pollos “cobb-500” - Venturo Espejo, Leidy Janeth (2019)
The present investigation was carried out with the objective of determining the effect of the use of meat flour in the production of Cobb-500 chickens in the fattening stage, carried out at the National University of Trujillo, also, to calculate the productive indicators of the broiler chicken cobb-500 and the evaluation of the optimum level of inclusion of meat meal, used in the feed at the stage of fattening of the chicken of the cobb.500 line. 80 birds of the cobb-500 line were used, under an experimental research design. Where the following parameters were evaluated: weight gain, feed conversion and mortality rate; data that were analyzed in the Excel program for analysis of variance and comparison of means. Where the results were: 1359.4 gr in weight gain, 1.09 feed conversion and 1.25% mortality rate. It is concluded that meat meal (PROTEIKA) can be used in rations of cobb-500 broilers in a range of 2% to 6% in the fattening stage.